The Impact of Educational Attainment and Work Tenure on Employee Performance: A Managerial Perspective - Soebiantoro; Nik Haryanti (Journal of Educational Management Research, 2025)
This study investigates the influence of educational attainment and work tenure on employee performance within the public sector, specifically at the Sumbergempol District Office in Tulungagung, Indonesia. Employing a quantitative, non-experimental research design, data were collected through questionnaires distributed to all 36 employees, constituting a population study. Data analysis was conducted using multiple regression techniques to determine the relationship between the independent variables—education level and length of service—and employee performance. The results reveal a significant positive correlation: employees with higher educational qualifications and longer work experience tend to demonstrate superior performance. These findings highlight the critical role of human capital development in enhancing organizational effectiveness. From a managerial perspective, the study underscores the importance of strategic investment in employee education and long-term career development. Public institutions, in particular, can benefit from aligning HR practices with policies that promote continuous learning and retention of experienced personnel. Enhancing both educational qualifications and job experience is not only beneficial for individual growth but also vital for improving overall public service delivery.